1999
DOI: 10.1016/s0896-6273(00)81035-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the E6-AP Ubiquitin Ligase Reduces Nuclear Inclusion Frequency While Accelerating Polyglutamine-Induced Pathology in SCA1 Mice

Abstract: Mutant ataxin-1, the expanded polyglutamine protein causing spinocerebellar ataxia type 1 (SCA1), aggregates in ubiquitin-positive nuclear inclusions (NI) that alter proteasome distribution in affected SCA1 patient neurons. Here, we observed that ataxin-1 is degraded by the ubiquitin-proteasome pathway. While ataxin-1 [2Q] and mutant ataxin-1 [92Q] are polyubiquitinated equally well in vitro, the mutant form is three times more resistant to degradation. Inhibiting proteasomal degradation promotes ataxin-1 aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
279
2
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(307 citation statements)
references
References 52 publications
19
279
2
7
Order By: Relevance
“…The SCA1 pathology correlates with the appearance of nuclear aggregates containing the mutated protein (7) but whether the aggregate formation is a symptom or cause of the disease is still a matter of debate (8 -10). The aberrant ataxin-1 either in its soluble form or in the form of aggregates was shown to be toxic to neurons supporting the notion that the poly-Q tract itself may play a critical role in SCA1 pathogenesis (7)(8)(9)(10)(11)(12). It may interfere with neuronal transcription by interacting with specific transcription factors in a poly-Q-dependent manner and induce apoptotic cell death (13).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…The SCA1 pathology correlates with the appearance of nuclear aggregates containing the mutated protein (7) but whether the aggregate formation is a symptom or cause of the disease is still a matter of debate (8 -10). The aberrant ataxin-1 either in its soluble form or in the form of aggregates was shown to be toxic to neurons supporting the notion that the poly-Q tract itself may play a critical role in SCA1 pathogenesis (7)(8)(9)(10)(11)(12). It may interfere with neuronal transcription by interacting with specific transcription factors in a poly-Q-dependent manner and induce apoptotic cell death (13).…”
mentioning
confidence: 71%
“…2C). Only at the temperature of 70°C and higher the structure formed by the helices H4 and 14 12-1-1-1-14 ⌬ ϭ Ϫ2 29 (CAG) 16 CAUCAGCAU (CAG) 10 16-1-1-1-10 ⌬ ϭ ϩ6 (CAG) 12 CAU (CAG) 16 12-1-16 ⌬ ϭ Ϫ4 30 (CAG) 12 CAUCAGCAU (CAG) 15 12-1-1-1-15 ⌬ ϭ Ϫ3 (CAG) 13 CAUCAGCAU (CAG) 14 13-1-1-1-14 ⌬ ϭ Ϫ1 31 (CAG) 11 CAUCAGCAUCAGCAU (CAG) 15 11-1-1-1-1-1-15 ⌬ ϭ Ϫ4 32 (CAG) 14 CAUCAGCAU (CAG) 15 14-1-1-1-15 ⌬ ϭ Ϫ1 (CAG) 12 CAUCAGCAU (CAG) 17 12- H3 was melted and all internucleotide bonds of that region showed similar reactivity. The structures formed by the repeats containing asymmetrically located interruptions are somewhat different (Fig.…”
Section: Cag Repeats Containing Either One or Two Cau Interruptions Umentioning
confidence: 99%
See 1 more Smart Citation
“…30 This would imply that nuclear localization is essential for pathology; however, mutations in E6-AP ubiquitin ligase reduce nuclear inclusion frequency, but accelerate disease, in this transgenic model. 31 These observations indicate that the soluble form of mutant ataxin-1 is pathogenic when the protein localizes to the nucleus but that nuclear aggregate formation is not essential for disease progression. Similar findings have been made in a culture model of CAG-repeat expansion disease.…”
Section: Dominantly Inherited Neurologic Diseases Induced By Nucleotimentioning
confidence: 95%
“…Although the protein aggregation and formation of inclusion bodies are commonly observed among these diseases, recent reports indicated that intracellular aggregation does not confer the cellular toxicity (Saudou et al, 1998;Cummings et al, 1999;Chun et al, 2002;Watase et al, 2002), rather the protective effect as they sequester the insoluble aggregation of mutant proteins (Arrasate et al, 2004). Finally, Kayed et al (2003) showed that the monomeric or oligomeric fibrous conformation of mutant proteins termed amyloid might induce neuronal toxicity, which is commonly seen among these diseases.…”
mentioning
confidence: 99%